2004
DOI: 10.3354/meps280249
|View full text |Cite
|
Sign up to set email alerts
|

Fishing effects on diversity, size and community structure of the benthic invertebrate and fish megafauna on the Bay of Biscay coast of France

Abstract: Within the framework of the 'dynamic equilibrium model', we tested the hypothesis that fishing causes major disturbance to benthic communities on deeper bottoms of the continental shelf. Benthic megafauna on the Bay of Biscay coast of France was sampled on fishing grounds subject to various conditions of exploitation. Samples were taken at around 100 m depth to avoid strong natural disturbances. Species diversity and the largest body mass class of invertebrates were smaller in strongly exploited areas than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 38 publications
2
53
0
1
Order By: Relevance
“…Within the Mediterranean Sea Gristina et al (2006) also found that heavily fished areas showed significantly lower Δ* and Δ+ values than areas of no or low fishing pressure. On the other hand, Blanchard et al (2004) found no difference between these indices in strongly versus moderately exploited areas of the Bay of Biscay. Again, conflicting results suggest that further research is needed on the responses of these indices to fishing.…”
Section: Comparison Between the Cimr And Fished Areasmentioning
confidence: 64%
“…Within the Mediterranean Sea Gristina et al (2006) also found that heavily fished areas showed significantly lower Δ* and Δ+ values than areas of no or low fishing pressure. On the other hand, Blanchard et al (2004) found no difference between these indices in strongly versus moderately exploited areas of the Bay of Biscay. Again, conflicting results suggest that further research is needed on the responses of these indices to fishing.…”
Section: Comparison Between the Cimr And Fished Areasmentioning
confidence: 64%
“…Not surprisingly, the abundance of small mobile deposit feeders and carnivores increased and large epibenthic sessile species decreased ). In the 2000s, comparison of locations exposed to different trawling frequencies gave similar results (Blanchard et al 2004). As trawling has been widespread for about 100 years in the Bay of Biscay, it is clear that the benthic community on the Grande Vasière was impacted in the early 1990s due to both a direct impact of trawling and a possible indirect impact mediated by a change in habitat suitability (Table 2).…”
Section: Offshore Benthosmentioning
confidence: 67%
“…levelling habitat structure along with species loss, see Thrush et al, 2001;Thrush and Dayton, 2002), on community size spectra, trophic positions and derived energy flow patterns (Hiddink et al, 2006a;Jennings et al, 2001bJennings et al, , 2002a, as well as on benthic community functioning as indicated by biological trait composition (e.g. Blanchard et al, 2004;Tillin et al, 2006). Previous studies of trawling effects on trophic structure suffered from methodological problems: they either compared subsystems only, such as fish communities (e.g.…”
Section: Introductionmentioning
confidence: 99%